2012
DOI: 10.1038/jcbfm.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Appraisal of Experimental Intracerebral Hemorrhage Research

Abstract: The likelihood of translating therapeutic interventions for stroke rests on the quality of preclinical science. Given the limited success of putative treatments for ischemic stroke and the reasons put forth to explain it, we sought to determine whether such problems hamper progress for intracerebral hemorrhage (ICH). Approximately 10% to 20% of strokes result from an ICH, which results in considerable disability and high mortality. Several animal models reproduce ICH and its underlying pathophysiology, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 127 publications
(202 reference statements)
1
66
0
Order By: Relevance
“…The major barriers to translational success identified in these workshops were a lack of rigorous standards and transparency in reporting preclinical studies, similar to what was reported by der Worp (2005) in ischemia stroke research and by MacLellan et al (2012) in intracerebral hemorrhage research. The subsequent published guidelines from these groups outline some of the principles and standards of good study design and report when conducting preclinical trials of candidate therapeutics-e.g., allocation concealment, blinded assessment of outcome, random allocation of subjects to experimental groups, and other methods designed to minimize bias and Type 1 (''false positive'') errors.…”
Section: How Can We Improve Benefits?mentioning
confidence: 57%
See 1 more Smart Citation
“…The major barriers to translational success identified in these workshops were a lack of rigorous standards and transparency in reporting preclinical studies, similar to what was reported by der Worp (2005) in ischemia stroke research and by MacLellan et al (2012) in intracerebral hemorrhage research. The subsequent published guidelines from these groups outline some of the principles and standards of good study design and report when conducting preclinical trials of candidate therapeutics-e.g., allocation concealment, blinded assessment of outcome, random allocation of subjects to experimental groups, and other methods designed to minimize bias and Type 1 (''false positive'') errors.…”
Section: How Can We Improve Benefits?mentioning
confidence: 57%
“…Additionally, there were obvious significant methodological differences between pre-clinical and clinical trials, in that the animals used were generally young and healthy before the experimentally induced stroke, while human patients were often elderly and hypertense (Macleod and Sandercock 2005). The same sort of shortcomings was also identified in studies on intracerebral hemorrhage (MacLellan et al 2012).…”
Section: Assessment Of Likelihood That Potential Benefitsmentioning
confidence: 71%
“…Firstly, these studies used different experimental models, the blood injection rat model or the collagenase injection mouse model. The blood injection and collagenase injection models are most often used but differ in many aspects (12,(14)(15)(16). Hematoma rapidly accumulates in the brain parenchyma in the clinical setting.…”
Section: █ Discussionmentioning
confidence: 99%
“…Recent clinical failures call into question whether these models accurately reflect human ICH, and whether they will be useful in successfully translating treatments from the laboratory. 32 Nevertheless, the FC infusion model is currently used for studying sex dimorphic long-term neurological deficits after ICH.…”
Section: Animal Models Of Ichmentioning
confidence: 99%